Country Economic Memorandum for Sao Tome and Principe - Background Note 1 : Economic Growth and Volatility in São Tomé and Príncipe - Barroso, Rafael (World Bank, Washington, DC, 2019)
The purpose of this background note is to give an overview of the literature on output volatility and economic growth, assess output volatility and its impact in São Tomé and Príncipe (STP). This note is organized in four sections, besides this introductory part. The second section reviews the literature on the impact of output volatility on economic growth. The third section discusses different measures of volatility, calculating volatility for STP across different periods, and compares them to peer countries. The last section offers some policy recommendations. Output volatility and its relationship with growth have been a hot topic in economic research literature for a long time. There is significant controversy about how economic volatility1 affects economic growth. Although the link between economic growth and volatility is theoretically ambiguous, a negative impact of economic volatility on output growth dominates the empirical literature. This negative relationship also holds with newer and better datasets, advanced econometrics methodologies, and for specific country groups. There are three mains messages in this note. The first one is that volatility affects growth as supported by the literature review and the econometric estimations carried out in this note. The second one is that STP is a volatile country, although volatility of GDP growth and inflation has declined over time and are in line with peers. On the other hand, STP still faces higher volatility on current account balances and net lending and borrowing than its peers. The third message is that, on average, a fifty percent increase in volatility translates into a 25 percent decrease in GDP per capita growth rates. Finally, policy measures aimed at diversifying exports in terms of goods and markets, reduce the reliance on external finance and fiscal rules can help cushion the volatility and reduce its impact.